Unusual Formation of CoO@C "Dandelions" Derived from 2D Kagóme MOLs for Efficient Lithium Storage. Issue 13 (25th January 2018) - Wu, Fangfang; Zhang, Shanshan; Xi, Baojuan; Feng, Zhenyu; Sun, Di; Ma, Xiaojian; Zhang, Junhao; Feng, Jinkui; Xiong, Shenglin
Abstract: Despite great breakthroughs, the search for anode materials with high performance for lithium‐ion batteries (LIBs) remains challenging. Hence, engineering advantageous structures via effective routes can bring new possibilities to the development of the LIB field. Herein, the precise synthesis of three‐dimensional (3D) hybrids of ultrathin carbon‐wrapped CoO (CoO@C) dandelions is reported by the pyrolysis of two‐dimensional (2D) Kagóme metal–organic layers (MOLs) at 400 °C under an Ar atmosphere. Due to the special coordination structure of the paternal MOLs, the resulting CoO nanowires show a small diameter of 5–10 nm and are uniformly confined within the ultrathin carbon layer. Based on the time‐dependent pyrolysis experiments, a crystal transformation mechanism of in situ self‐templated‐recrystallization‐self‐assembly accompanied by phase and morphology changes is first presented to reveal the formation of the 3D dandelion‐like spheres with assembly of nanowire arrays from a 2D Kagóme MOL. By virtue of structural and compositional features, including a 3D array structure, the small size of the primary ultrathin nanowires, and a uniform ultrathin graphitic carbon layer, these unique CoO@C dandelions display high specific capacity, good rate capability, and excellent cycling stability. Importantly, this approach can be extended to accurately synthesize other desired composite structures. Abstract : A novel 3D hybrid dandelion‐like nanowire array with ultrathin CoO nanowires enwrapped by ultrathin carbon is synthesized from a 2D Kagóme metal–organic layer. Originating from unique compositional and structural features, the as‐derived dandelions indicate excellent lithium storage properties.